Feasibility of colonoscopy with water infusion in minimally sedated patients in an Asian Community Setting - Hsieh, Yu-Hsi (Landes Bioscience, 2011)
BACKGROUND: Investigators in the US described large volume water infusion with marked benefits but acknowledged the limitation of male veteran predominance in the study subjects. The aim of this study was to assess the feasibility of large volume water infusion in Asian patients undergoing minimal sedation diagnostic colonoscopy in a community setting. METHODS: Consecutive patients who underwent colonoscopy were randomized to receive large volume (entire colon) (Group A, n=51), limited volume (rectum and sigmoid colon) (Group B, n=51) water infusion, or air insufflation (Group C, n=51). Pain during insertion, completion rate, cecal intubation and total procedure times, and patient satisfaction were evaluated. Pain and satisfaction were assessed with a 0–10 visual analog scale. RESULTS: The mean pain scores during insertion were lower in the Group A and Group B than in Group C, 3.3±2.4, 3.0±2.2 and 4.4±2.6, respectively (p=0.028 and p=0.004). The completion rates and cecal intubation times were similar among the three groups. The procedure time was significantly longer in Group A than in group C (15.3±5.9 min vs. 13.1±5.4 min, p=0.049). Overall satisfaction with the procedure was greater in Group B than in Group C only (9.7±0.5 vs. 9.4±0.8, p=0.044). CONCLUSIONS: Diagnostic colonoscopy with large volume water infusion without air insufflation appears to be feasible in minimally sedated Asian patients in a community setting. Measures to improve the outcome further are discussed.